ASSESSMENT OF SERUM ZINC LEVEL IN PATIENTS WITH POLYCYSTIC OVARY SYNDROME (Iraqi Journal of Medical Sciences, 2017)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine-metabolic disorder affecting women of reproductive age characterized by multiple hormonal imbalances, reflecting on a clinical presentation dominated by manifestations of hyperandrogenism, which generate short and long term consequences on female health. Skin is a major target for androgen activity, several hyperandrogenemia-triggered dermatologic alterations can be seen in PCOS, most commonly hirsutism, androgenic alopecia, acne, seborrhea, onycholysis, and onychorrhexis. Zinc is one of the most important trace elements required as a catalytic, structural, and regulatory ion for the activities of more than 300 enzymes, proteins, and transcriptional factors. Zinc insufficiency in the female can lead to complications such as impaired synthesis/secretion of follicular stimulating hormone (FSH) and luteinizing hormone (LH), abnormal ovarian development.Objective: To assess serum zinc level in patients with PCOS.Methods: A case-controlled study was conducted in Al-Imamein Al-Kadhemein Medical City from the period of March to June 2016. Eighty females were enrolled in this study; their age ranged from 20 to 32 years. They were divided into 4 groups: Group I: Twenty patients with PCOS with body mass index (BMI) ranged from 30.0-40.0. Group II: Twenty normal healthy control obese ladies with BMI ranged from 30.0-40.0. Group III: Twenty patients with polycystic ovary syndrome with BMI ranged from 18.5-29.9. Group IV: Twenty females as a healthy control non-obese ladies with BMI ranged from 18.5-29.9.Results: Serum zinc level was significantly decreased in obese PCO group than in non-obese PCO group. Serum prolactin (PRL) level and LH levels were elevated in PCO group which was highly significant. There was negative correlation between serum zinc level and BMI in PCO patients. Also, negative correlation was observed between serum zinc level and serum PRL level in non-obese PCO patients.Conclusion: Serum zinc level reduced in obese PCOS than in non-obese PCO.Keywords: Serum zinc level, polycystic ovary syndromeCitation: Iqbal G. Farhood. Assessment of serum zinc level in patients with polycystic ovary syndrome. Iraqi JMS. 2017; Vol. 15(1): 39-47. doi: 10.22578/IJMS.15.1.6
Keywords: Serum zinc level; polycystic ovary syndrome